Pengaruh Pemberian Vermikompos dan Pupuk KNO3 terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium Ascalonicum L.) pada Lahan Kering - Ajeng Melanea Dea Pitaloka; Usmadi Usmadi (Jember University Press, 2023)
The use of dry land for shallot cultivation in Indonesia is still not optimal because it is considered as land that has no good potential for crop cultivation. Dry land problems include limited availability of water, low organic matter and soil nutrients, especially potassium. The purpose of this experiment was to determine the response of vermicompost and KNO3 fertilizer to the growth and yield of shallots on dry land. The experimental design used a factorial randomized block design, doses of vermicompost (5 tons/ha, 10 to/ha, and 15 tons/ha) and KNO3 fertilizer doses (0 kg/ha, 114 kg/ha, and 228 kg/ha). Parameters observed included plant height, number of leaves per hill, number of tubers per hill, tuber diameter, weight of fresh tubers per hill, weight of stored dry tubers per hill, and tuber moisture content. The results showed that the interaction between the application of 10 tons/ha of vermicompost and 114 kg/ha of KNO3 fertilizer had a significant effect on the parameters of fresh tuber weight per clump and dry tuber weight stored per clump. The single treatment of vermicompost at a dose of 15 tons/ha had a significant effect on plant height, number of leaves per hill, fresh tuber weight per hill, and dry tuber weight stored per hill. Single treatment with KNO3 fertilizer dose of 228 kg/ha had a significant effect on the weight of fresh tubers per clump and the weight of stored dry tubers per clump.